Vicisitudes de la contratación eventual - Armanini, Mariano Ángel (2009)
Temporary employment contracts have raised not few objections and\ndoubts within the labor environment. Especially, when these contracts are entered\ninto not directly by the employer, but through the so-called temporary service\ncompanies, producing a triangulation in the employment relationship (user\ncompany, temporary service company, and temporary worker) and, at the same\ntime, the dissociation of employer?s rights (user company and temporary service\ncompany).\nWithin this topic, there are two issues. One is that regarding the possibility of\nalleging the test period, unfavorable to the worker, in general, and particularly to the temporary worker. The other issue is the compliance with hygiene and safety\nstandards at the workplace